Essentialism the disciplined pursuit of less - McKeown, Greg. (New York Crown Business, 2014)
In Essentialism, Greg McKeown, CEO of a leadership and strategy agency in Silicon Valley who has run courses at Apple, Google and Facebook, shows you how to achieve what he calls the disciplined pursuit of less. Being an essentialist is about a disciplined way of thinking. It means challenging the core assumptions of "we can have it all" and "I have to do everything" and replacing them with the pursuit of "the right thing in the right way at the right time".
Includes bibliographical references and index.
Keywords: Choice (Psychology)